2010
DOI: 10.4314/sljbr.v2i1.56592
|View full text |Cite
|
Sign up to set email alerts
|

Parasites Associated with Sachet Drinking Water (Pure Water) in Awka, South-Eastern, Nigeria

Abstract: A study to ascertain the parasites associated with sachet drinking water, (popularly called "Pure Water" in Nigeria), in Awka, capital of Anambra State, southeast Nigeria was conducted. This was in order to determine the safety and suitability of such water for human consumption. Sachet water is a major source of drinking water for low and middle class Nigerians. The increase in demand of this water has led to the proliferation of industries in this sector, because of the economic benefits derivable from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This is in line with the findings of some other authors in Nigeria and outside (Addo et al, 2009). However, the occurrence of these isolates in sachet water used in this study is in contrast with the findings of some other studies in Nigeria which found no enteric pathogens (Egwari et al, 2005;Ekwunife et al, 2010). Our findings also differ from other study in that no E. coli and E. faecalis were recovered as was reported in a study by Oyedeji et al (2010).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the findings of some other authors in Nigeria and outside (Addo et al, 2009). However, the occurrence of these isolates in sachet water used in this study is in contrast with the findings of some other studies in Nigeria which found no enteric pathogens (Egwari et al, 2005;Ekwunife et al, 2010). Our findings also differ from other study in that no E. coli and E. faecalis were recovered as was reported in a study by Oyedeji et al (2010).…”
Section: Discussionsupporting
confidence: 88%
“…The most occurring parasite observed in this study was Entamoeba spp (12.31%), followed by Cryptosporidium (10.00%). The peak occurrence rate of Entamoeba histolytica (45.3%) has been recorded by Ani and Itiba (2015), while Ekwunife et al (2010) and Anyanwu et al (2018) observed a lower and non peak prevalence of 4.8% and 3.2% in studies of domestic water sources. Entamoeba histolytica is the principal aetiologic agent of human amoebiasis.…”
Section: Discussionmentioning
confidence: 85%
“…It therefore indicates that the water samples contain no pathogens.A similar result was obtained by Egwari et al (2005) in Lagos, South West of Nigeria who in their bacteriology study of sachet water found no Enteric pathogens and Entamoeba coli. More so, Ekwunife et al (2010) carried out a similar study in Awka, South Eastern Nigeria, and no protozoan parasites were detected in sachet drinking water used for their study. However, Alli et al(2011) observed occurrence of parasites in some sampled sachet water in the South West of Nigeria.…”
Section: Adequatementioning
confidence: 98%